CREATIVE APPROACHES OF INTELLECTUALS IN THE SCIENTIFIC DEVELOPMENT OF NEW UZBEKISTAN (International Conference on Educational Discoveries and Humanities, 2025)
This article analyzes the contribution of creative intellectuals to the development of science and modern scientific approaches in the development of Uzbekistan. The importance of modern scientific paradigms formed on the basis of scientific and innovative achievements and cultural heritage is revealed. The article also notes that the foundation of the Third Renaissance is being formed precisely through the education system, and talks about the reforms being implemented in the country.